Characterization of the innervation of the meibomian glands in humans, rats and mice - Bründl, Maximilian; Garreis, Fabian; Schicht, Martin; Dietrich, Jana; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2020)
Aim of the present study was to identify the nerve structures of meibomian glands in humans, rats and mice into sympathetic, parasympathetic and sensory parts as well as their topographical relation with regard to the gland architecture. The upper and lower eyelids of humans, rats and mice were examined by means of immunohistochemistry and indirect immunofluorescence. Specimen were investigated with antibodies against vesicular acetylcholine transporter (VAChT), tyrosine hydroxylase (TH), nitric oxide synthase (NOS), and calcitonin gene-related peptide (CGRP). For overview and general identification of the nervous structures, protein gene product 9.5 (PGP 9.5) was used. PGP-immunoreactive nerve fibers were detectable in the interstitium of the meibomian glands, especially in the neighborhood to the basement membrane of the acini. The axons were positive for CGRP, VAChT, TH and NOS. In addition, the fluorescence labeling also revealed isolated nerve endings surrounding the duct system of the glands, especially along the main duct and in adjacent blood vessels. The density of the innervation of the meibomian glands and the detection of various neuropeptides suggest an influence of the nervous system on the function of the glands. To what extent these may play a role in the modulation of glandular function and the pathogenesis of dry eye disease, or perhaps even represent a possible therapeutic approach, needs further investigation.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Innervation; Meibomian gland; Neurotransmitter; Ocular surface; Tear film